Inovasi Pelayanan Pencatatan Pernikahan Melalui E-Kartu Nikah Di Kantor Urusan Agama Kecamatan Ilir Timur II Kota Palembang - Ari Biyantino Pratama; Ivana Ivana; Trecy Austin (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted at KUA Ilir Timur II Palembang City. This study aims to find out how the E-Marriage Card Innovation is at the Religious Affairs Office of Ilir Timur II District. Those who have implemented the E-Marriage Card innovation since 2019. The research method is a aqulitative descriptive approach, with data collection techniques through interviews, observations, and interviews. Documentation. Based on the Regulation of the Minister of Religion Article 21 paragraph 1 20/2019, the husband and wife get a marriage regitration book and marrige card. This marriage registration innovation is called E-Marriage Card. The results of the study indicate that, when viewed as a whole, the 5 innovation indicators are relative advantage, compatibility, complexity, variability, observability. The researcher concludes that the E-Marriage Card innovation has good innovation characteristics. Able to provide marriage registration services in accordance with the needs of the community. The government has succeeded in replacing manual services with technology-based innovations. However, if viewed from several aspects, there are still obstacles in the implementation of the innovation, namely the lack of understanding of some people regarding the procedure or flow of marriage registration through E-Marriage Cards. So that it becomes an obstacle for the process of making E-Marriage Card. Because basically all contents of the E-Marriage Card innovation data are managed to be recorded and connected to the Simkah Web which is then also integrated with the civil registry. So if there is an error or data change, it must be changed first in the capil because the data cannot be changed through the SIMKAH WEB application. In addition, network problems are also one of the obstacles in implementing these innovations.